Ammonia-induced autophagy is independent of ULK1/ULK2 kinases - Cheong, Heesun (National Academy of Sciences, 2011)
Autophagy, a lysosome-mediated catabolic process, contributes to maintenance of intracellular homeostasis and cellular response to metabolic stress. In yeast, genes essential to the execution of autophagy have been defined, including autophagy-related gene 1 (ATG1), a kinase responsible for initiation of autophagy downstream of target of rapamycin. Here we investigate the role of the mammalian Atg1 homologs, uncoordinated family member (unc)-51–like kinase 1 and 2 (ULK1 and ULK2), in autophagy by generating mouse embryo fibroblasts (MEFs) doubly deficient for ULK1 and ULK2. We found that ULK1/2 are required in the autophagy response to amino acid deprivation but not for autophagy induced by deprivation of glucose or inhibition of glucose metabolism. This ULK1/2-independent autophagy was not the simple result of bioenergetic compromise and failed to be induced by AMP-activated protein kinase activators such as 5-aminoimidazole-4-carboxamide riboside and phenformin. Instead we found that autophagy induction upon glucose deprivation correlated with a rise in cellular ammonia levels caused by elevated amino acid catabolism. Even in complete medium, ammonia induced autophagy in WT and Ulk1/2(−/−) MEFs but not in Atg5-deficient MEFs. The autophagy response to ammonia is abrogated by a cell-permeable form of pyruvate resulting from the scavenging of excess ammonia through pyruvate conversion to alanine. Thus, although ULK1 and/or ULK2 are required for the autophagy response following deprivation of nitrogenous amino acids, the autophagy response to the enhanced amino acid catabolism induced by deprivation of glucose or direct exposure to ammonia does not require ULK1 and/or ULK2. Together, these data suggest that autophagy provides cells with a mechanism to adapt not only to nitrogen deprivation but also to nitrogen excess.